Quantitative Approach of Sterculia setigera Del. (Sterculiaceae) Ethnobotanical Uses Among Rural Communities in Togo (West Africa) - Atakpama, Wouyo; Batawila, Komlan; Gnamkoulaba, Atama; Akpagana, Koffi (Ethnobotany Research and Applications, 2015)
Abstract The relationship between human, their culture and their environment has high importance in the frame of sustainable management of natural resources. This study aimed to assess the local uses of Sterculia setigera within rural communities in Togo. The methodology followed during this study was based on inquiries. Fifteen ethnic groups were involved. The interethnic convergence was assessed by using 4 use indices: reported use, plant part value, specific reported use, and intraspecific use value. The mean reported uses showed significant difference between geographic zones, ethnic groups, age, and corporations; but no significant difference between genders. Pharmacopeia (67.00 %), followed by magicomystic (15.23 %), and food (10.43 %) were the main quoted uses. The most used organ is the bark. Decoction was mentioned as the most used method of preparation. Considering the socio-economic and cultural importance of this species, it is important to promote its integration in agroforestry systems. Résumé Le rapport entre être humain, leur culture et leur environnement est d’une grande importance dans le cadre de gestion durable de ressources naturelles. La présente étude compte déterminer les usages locaux de Sterculia setigera au sein des communautés rurales du Togo. La méthodologie suivie au cours de cette étude a été basée sur les enquêtes. Quinze groupes ethniques ont été impliqués. La convergence d’usage interethnique a été étudiée en utilisant 4 indices d’usage: l’usage rapporté, la valeur de l’organe, l’usage spécifique rapporté, et la valeur d’usage interspécifique. Les moyennes d’usages rapportés montrent une différence significative entre les zones géographiques, les groupes ethniques, l’âge et les corporations. Par contre, aucune différence significative n’existe entre les genres. La pharmacopée (67.00%), suivi par l’usage magico-mystique (15.23%), et alimentaire (10.43%) était les principales catégories d’usages rapportés. L’organe le plus usagé est l’écorce et la décoction est le mode de préparation la plus cité. Compte tenu de l’importance socio-économique et culturelle de cette espèce, il est opportun d’encourager son intégration dans les systèmes agroforestiers.